2020
DOI: 10.1182/bloodadvances.2019000133
|View full text |Cite
|
Sign up to set email alerts
|

Induction of blood-circulating bile acids supports recovery from myelosuppressive chemotherapy

Abstract: Chemotherapeutic agents can reduce bone marrow (BM) activity, causing myelosuppression, a common life-threatening complication of cancer treatment. It is challenging to predict the patients in whom prolonged myelosuppression will occur, resulting in a delay or discontinuation of the treatment protocol. An early indicator of recovery from myelosuppression would thus be highly beneficial in clinical settings. In this study, bile acids (BAs) were highly increased in the systemic circulation as a natural response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Addition of a chemical ER stress inducer, tunicamycin, increased the ratio of CD244 + HSCs within CD48 − KSL cells ( Figures 4 A and 4B). Conversely, addition of TUDCA, a BA known to suppress ER stress ( Miharada et al., 2014 ; Özcan et al., 2006 ; Sigurdsson et al., 2020 ), resulted in increased frequency of CD244 − HSCs ( Figures 4 A and 4B). Of note, the frequency of KSL cells did not significantly differ in both cases and CD48 negativity was marginally affected while the frequency of CD244 − CD48 - population in KSL was significantly changed ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…Addition of a chemical ER stress inducer, tunicamycin, increased the ratio of CD244 + HSCs within CD48 − KSL cells ( Figures 4 A and 4B). Conversely, addition of TUDCA, a BA known to suppress ER stress ( Miharada et al., 2014 ; Özcan et al., 2006 ; Sigurdsson et al., 2020 ), resulted in increased frequency of CD244 − HSCs ( Figures 4 A and 4B). Of note, the frequency of KSL cells did not significantly differ in both cases and CD48 negativity was marginally affected while the frequency of CD244 − CD48 - population in KSL was significantly changed ( Figure 4 B).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the BA ursodeoxycholic acid (UDCA) is routinely used in clinics in the context of BM transplantation, where supplementation with UDCA has been shown to reduce post-transplant complications and improve overall survival 62 . Available reports have attributed these benefits to the unique feature of tauro-conjugated form of UDCA (TUDCA) as chemical chaperones, improving protein folding in fetal liver HSCs 38 or after acute BM insult 39 . In addition, UDCA and TUDCA are hydrophilic BAs, and part of their beneficial effects could be a consequence of changes in the hydrophobicity of the BA pool 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TGR5 expression was observed in human BMSC-derived adipocytes 32 , but the effect of TGR5 on BMAT and thus on BM function is unknown. Previous reports have shown that BAs impact fetal and adult hematopoiesis acting as chemical chaperones [37][38][39] and, more recently, through direct interaction with myeloid blood cell precursors via the vitamin D receptor 40 . However, the effects at the level of TGR5, a BA-specific and potentially druggable receptor, remain to be unraveled.…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids (BAs) are well known as chemical chaperones to reduce endoplasmic reticulum stress in hematopoietic stem cells ( Oguro, 2019 ). Recently, BA was reported to play a key role in the reconstitution of hematopoiesis and BA levels in the blood of pediatric cancer patients and mice treated with chemotherapeutic agents were increased in synchrony with an early proliferation of bone marrow cells and recovery from myelosuppression ( Sigurdsson et al, 2020 ). BA metabolism pathway was found significantly enriched in the high-risk group, proving further evidence that dysregulated cholesterol homeostasis might result in ferroptosis resistance and promote tumorigenicity and metastasis in cancer ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%